Pola Komunikasi Antarbudaya Mertua dan Menantu Beda Etnis - Stefanny Cristina Marsaulina Siahaan; Ahmad Junaidi (Koneksi, 2019)
Researchers want to find out how the communication patterns that exist between parents in-laws and son or daughter in-laws who had different ethnic backgrounds. Communication in a family is an important aspect in terms of establishing good relations between families and building harmonious relationships, especially in couples in-laws. Communication that exists between the three couples parents in law and son or daughter in-laws who had different ethnic backgrounds. The researcher also wanted to find out what barriers to intercultural communication the three couple parents-in-law and son or daughter-in-law went through. The method used by the researchers in this research was a descriptive qualitative research method using in-depth interview by three couple parents in-laws and son or daughter in-law and also a literature study. After conducting research on three couple parents in law and son or daughter in-law, the three couples have gone through a long communication process, and the communication patterns established between the three couples are not different, all three had a transactional communication model, because the three parents-in-law and son or daughter-in-law are both recipients and the sender of the message in a continuous and responsible for the impact and effectiveness of the communication that occurs. barriers in intercultural communication experienced by these three couple parents-in-law and son or daughter-in-law, based on the Nine barriers of intercultural communication presented by Chaney & Martin (2004). The nine obstacles were not experienced by the three couple parents-in-law and the son or daughter in-law. Peneliti ingin mengetahui bagaimana pola komunikasi yang terjalin antara mertua dan menantu yang berbeda latar belakang etnis. Komunikasi dalam sebuah keluarga merupakan aspek penting dalam hal menjalin hubungan baik antar keluarga dan membangun hubungan yang harmonis terutama pada pasangan menantu dan mertua. Komunikasi yang terjalin antara ketiga pasangan menantu dan mertua ini memiliki latar belakang etnis yang berbeda. Peneliti juga ingin mengetahui apa saja hambatan komunikasi antarbudaya yang dilalui ketiga pasangan mertua dan menantu tersebut Metode yang digunakan peneliti dalam penelitian ini adalah metode penelitian deskriptif kualitatif dengan menggunakan teknik pengumpulan data wawancara mendalam dengan tiga pasangan menantu dan mertua dan juga studi kepustakaan. Setelah melakukan penelitian kepada tiga pasangan menantu dan mertua, ketiga pasangan tersebut telah melalui proses komunikasi yang panjang, dan pola komunikasi yang terjalin antara ketiga pasangan tersebut tidak berbeda, ketiganya memiliki model komunikasi transaksional, karena ketiga pasangan mertua dan menantu tersebut sama-sama menjadi penerima dan pengirim pesan dalam waktu yang berkelanjutan dan bertanggung jawab terhadap dampak dan efektivitas komunikasi yang terjadi. Hambatan komunikasi antarbudaya yang dialami ketiga pasangan mertua dan menantu ini, berdasarkan Sembilan hambatan komunikasi antarbudaya yang dipaparkan oleh Chaney & Martin (2004). Sembilan hambatan tersebut tidak dialami oleh ketiga pasangan mertua dan menantu tersebut.